2010
DOI: 10.1016/j.neures.2010.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin mediates the antidepressant effects of mating behavior in male mice

Abstract: A significant association between plasma oxytocin (OT) levels and depression has been demonstrated. A recent study found that sexual activity and mating with a female induced the release of OT in the central nervous system of male rats. Here we examined the effect of mating behavior on depression-related behavior in wild-type (WT) and OT receptor-deficient (OTR KO) male mice. The WT males showed a reduction in depression-related behavior after mating behavior, but the OTR KO mice did not. Application of an OTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Using a food-related fMRI paradigm, we demonstrated that AN and ANWR had fasting and post-prandial hypoactivation of the amygdala, a brain region involved in emotion, compared to healthy women, and post-prandial oxytocin secretion mediated a significant portion of this difference in AN 4, 5 . Animal data indicate that oxytocin has anxiolytic and antidepressant properties 6-10 . Oxytocin administration reduces symptoms in rodent models of anxiety and depression, and serotoninergic neurons may mediate these effects 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Using a food-related fMRI paradigm, we demonstrated that AN and ANWR had fasting and post-prandial hypoactivation of the amygdala, a brain region involved in emotion, compared to healthy women, and post-prandial oxytocin secretion mediated a significant portion of this difference in AN 4, 5 . Animal data indicate that oxytocin has anxiolytic and antidepressant properties 6-10 . Oxytocin administration reduces symptoms in rodent models of anxiety and depression, and serotoninergic neurons may mediate these effects 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Sexual activity and mating in male rats mediated anxiolysis via the release of OT in the CNS, specifically within the PVN [21]. A recent study showed that OT mediated the antidepressant-like effect of sexual activity and mating behavior in male mice [13]. For nonmating behavioral experiments, a male was placed with a female into a cage partitioned by a perforated acrylic wall allowing auditory, visual, and olfactory communication, but not physical contact.…”
Section: Sexual Activity Shows Antidepressant-like Effects Through Inmentioning
confidence: 99%
“…No reduction in the duration of immobility was seen 24 h after the mating behavior. However, the mice showing long-term mating behavior had a significantly reduced duration of immobility both 1 and 24 h after the termination of cohabitation compared with control mice [13]. In addition to the PVN, other regions of the brain, notably, the hippocampus, amygdala, and spinal cord, release OT to mediate sexual behavior [21].…”
Section: Sexual Activity Shows Antidepressant-like Effects Through Inmentioning
confidence: 99%
See 2 more Smart Citations